2008
DOI: 10.1080/17509653.2008.10671044
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary team building method based on competency modelling in design project management

Abstract: This research aims to develop a new team building method based on competency modelling in the field of project management. This method is divided into three main stages. First, a competency matrix based on a task-actor compatibility indicator helps to characterise the competency levels. Second, we apply a clustering algorithm in order to reduce the problem complexity and favour the employees' expertise. The clustering algorithm will decompose large sets of tasks and actors into smaller task groups related to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Bajaj and Russel (2008) combine ideas from social networks and work-flow modeling to optimize the overall cohesiveness of multiple work groups with an integer programming model. Hlaoittinun et al (2008) use a clustering algorithm and an integer program to build a single project team based on competency requirements. In the area of group technology and cellular manufacturing, researchers have employed goal programming to minimize deviations of objective measures from aspired levels.…”
Section: Prior Researchmentioning
confidence: 99%
“…Bajaj and Russel (2008) combine ideas from social networks and work-flow modeling to optimize the overall cohesiveness of multiple work groups with an integer programming model. Hlaoittinun et al (2008) use a clustering algorithm and an integer program to build a single project team based on competency requirements. In the area of group technology and cellular manufacturing, researchers have employed goal programming to minimize deviations of objective measures from aspired levels.…”
Section: Prior Researchmentioning
confidence: 99%
“…A more generic approach towards team composition has been proposed by Hlaoittinun et al [9]. They proposed to use array-based clustering in order to group aspects from the context with aspects belonging to the team itself.…”
Section: Team Compositionmentioning
confidence: 99%
“…A team building method based on competency modelling has been proposed in [28] for supporting project leaders to organise the actors into teams. The authors suggested that incorporating a clustering algorithm as a step of the method results in preserving expertise and thus helps project managers to find better trade-offs between project cost (short term goal) and competency dynamics (long term goal).…”
Section: A Algorithms and Modelsmentioning
confidence: 99%